Opening the black box of project team members’ competencies improvement in a public sector organization for a successful transition to the project society - France Desjardins; Éric Jean; Christophe Bredillet (Project Leadership and Society, 2022)
The purpose of this paper is to investigate the project team member's skill developmental activities within the context of a public organization, as to suggest both a theoretical understanding and a procedure adapted for this development, which is based on a reflective approach. The methodology used is based on a qualitative inductive approach subject to a single case study. For an organization with a lightweight project matrix structure to efficiently decentralize the various HR practices related to skill development, the skills evaluation must be self-administered, the development plan and training activities are integrated into the project's lessons learned sessions and support is offered to the project team by an external party (coach). The developmental approach through learning in an occupational environment also enables the organization to adapt to the project society with collaborative and qualified management. This original research stems from its descriptive and comprehensive approach to adapt project management and HRM theories to inform public management.